Multi-branched river flood routing by multiple-reach Muskingum model - عبدالرضا ظهیری; Fahimeh Mostakhdemin (رویکردهای نوین در مهندسی آب و محیط زیست)
Among the hydrological flood routing methods, due to simplicity and few required data, Muskingum model has always been considered. Until now, the application of this method in multi- branched rivers has been limited due to the lack of flood data. In Muskingum method, two parameters (x and K) are calibrated throughout the river. In this study, the Muskingum method was used to route floods in a multi-branched river. For this purpose, the multi-branched river system including the main waterway, tributary and the end of the river after the confluence is divided into several intervals and for each interval, the calculation procedure of the Muskingum model are performed separately. In this case, the multiple-reach Muskingum parameters will be obtained. The implementation of the multiple-reach Muskingum model in the branched system of Tajen River located in Mazandaran province showed that the triple reach model has the best accuracy. The sum of squared the errors for the single, double and triple Muskingum models were approximately 422, 262, and 222 (m3/s)2, respectively, indicating an acceptable accuracy of the flood routing results in the multiple-reach Muskingum model. The observed peak flow discharge of the outflow hydrograph from the Tajen river is about 61.7 m3/s and in single, double and triple Muskingum models are about 55.7, 58.3 and 58.9 m3/s, respectively. Also, the actual flood volume of outflow hydrograph was about 2.53 mcm while this volume in single, double and triple Muskingum is obtained as 2.50, 2.55 and 54 mcm, respectively.